Are horned cows in loose housing more stressed than hornless cows? a cross-sectional study in organic dairy farms - A. Ebinghaus; G. Thiessen; S. Ivemeyer; U. Knierim (Animal)
In commercial dairy farming, the majority of cows are dehorned or genetically hornless. It is argued that this reduces the risk of injurious and stressful social conflicts. On the other hand, in horned herds, management and housing may be better adapted to the cows, e.g. by avoiding changes in herd structure or by providing more space and resources, which would contribute to reducing stress. This cross-sectional study with 12 horned and 13 hornless organic dairy herds in loose housing aimed to explore the effect of horn status on faecal cortisol metabolites (FCMs) as an indicator for the cows’ stress level while taking into account possible differences in the farms’ compliance with management and housing recommendations for reducing social conflicts. Repeated faecal samples were collected from 674 cows (n = 2 625 samples), and FCMs were analysed by enzyme immunoassay. A total of 22 housing and management factors relating to guideline recommendations were recorded. Each factor was categorised as compliant, partly compliant, or non-compliant, and percentages of housing, management, and overall compliance were calculated. There was a wide variation in overall compliance between farms, ranging from 20 to 93%. Housing and management compliance correlated positively (rs = 0.62) and farms with horned cows complied with more recommendations (median: 60 vs 48%). A linear mixed model was calculated with the fixed effects of horn status, overall compliance, and their interaction. Cow was nested within herd as a random effect, and days in milk and time of sampling were included as covariates. FCM levels were not higher in horned compared to hornless herds. However, contrary to expectations, no associations with compliance were found. More knowledge is needed about the extent to which FCM levels reflect social stress and whether individual housing or management factors may be particularly important in reducing stress.